Marketing Politik Pemenangan Pasangan Kandidat Sri Juniarsih dan Gamalis dalam Kemenangan Pilkada Di Kabupaten Berau Tahun 2020 - Singka Hana Berlyn; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The research aims to describe how political marketing and the inhibiting factors of political marketing win the candidate pair Sri Juniarsih and Gamalis in winning the local elections in Berau Regency in 2020. The method used is a qualitative research method with a descriptive approach. This study uses primary data sources in the form of interviews, observations, and documentation, as well as secondary data from books or the internet. Data analysis techniques are data reduction, data presentation, and drawing conclusions. While the theory used in this research is political marketing theory with product, promotion, price and place variables according to Niffenegger (in Firmanzah, 2008). The results of the study show that Sri Juniarsih and Gamalis' political marketing in winning the regional elections in Berau Regency in 2020 can be said to be effective in attracting voters' votes so that they can become winners in the regional elections in Berau Regency in 2020. This can be seen from how Sri Juniarsih and Gamalis apply marketing variables Politics. The candidate offers a product in the form of a platform that contains a vision, mission and work program based on the main development challenges in Berau Regency, a supportive past record and has good personal character. Furthermore, promotions are carried out directly to voters, through figures or organizations as well as social media and mass media, because they have a major influence in attracting voter sympathy. In addition, candidates can provide good prices for their products, so that voters trust and form a good perception of the Sri Juniarsih and Gamalis pair. In determining the location, the candidate draws closer to the voters through meetings and visits and places campaign teams and volunteers in the villages to reach all levels of society. While the inhibiting factor in carrying out political marketing lies in the minimal and limited funds used in a series of political marketing processes.